PERUBAHAN GOLONGAN DARAH PADA PENDERITA LEUKEMIA MIELOBLASTIK AKUT - Losen Adnyana, IW; Suega, K (journal of internal medicine; Vol. 12, No. 1 Januari 2011, 2012)
We reported a case of acute leucemia (AML-M6) that experienced change of blood group. Leukemia is hematologic malignancy with differentiation abnormality at grades haematopoetic stem cell that can make progressive expansión from malignant clone cell in bone marrow and than spread to systemic circulation. In ABO blood system, group A with A antigen and anti B antibody, group B with B antigen and A antibody, O group without AB antigen and antibody. In this case, acute leukemia be con! rmed with blood smear and bone marrow puncture. Changes of blood group known after remission induction chemotherapy accordng to AML-M6 regiment. Post chemotherapy, there was changes O to A blood group according to ABO system. On family examination showed result of subgroup A of blood group previously. On acute leucemia or other hematopoitic disease, there are two mechanism for explanation change of ABO blood system. The ! rst hematologic malignancy induced loss of ABO antigen due to inactivity of transferae A and B as the result was loss or decreased of antigen A and or B with simultant increase of H antigen. Second, loss of ABH antigen in certain type of leucemia preceeding by loss of heterogenicity. ABO antigen will reversed after proper treatment of leucemiaitself.
Keywords: Acute leukemia, changes of blood group, chemotherapy